Refuge and Resistance: Palestinians and the International Refugee System - Irfan, Anne (New York : Columbia University Press, 2023)
"In the decades after World War II, the United Nations established a global refugee regime that became central to the lives of refugees around the world. This regime operated most acutely for Palestinian refugees, who were served by a specialized UN body: the Relief and Works Agency (UNRWA). Refuge and Resistance examines UNRWA's exchanges and interactions with Palestinian refugee communities, particularly in the camps where it functioned as a surrogate state. Grounded in empirical research-including previously unseen documents from UNRWA's own archive-this book shows how Palestinian refugees regularly invoked internationalist norms to demand their political rights, while resisting the UN's apolitical categorization of their plight as a humanitarian issue. This book thus re-conceptualizes the Palestinian refugee camps as internationalized spaces, and recasts the refugee communities as important historical actors in global politics. Providing the first international history of the Palestinian refugee camps, Refuge and Resistance offers a vital new perspective for understanding politics beyond the nation-state, in a region that remains central to international politics"
Keywords: Human rights advocacy -- Political aspects -- History -- Arab countries; Stateless persons -- Civil rights -- Arab countries; Refugees, Palestinian Arab -- Legal status, laws, etc. -- Arab countries; Refugee camps -- Arab countries; Refugees, Palestinian Arab -- Services for -- Middle East